If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -4(2k + -5) = 71 Reorder the terms: 3 + -4(-5 + 2k) = 71 3 + (-5 * -4 + 2k * -4) = 71 3 + (20 + -8k) = 71 Combine like terms: 3 + 20 = 23 23 + -8k = 71 Solving 23 + -8k = 71 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + -8k = 71 + -23 Combine like terms: 23 + -23 = 0 0 + -8k = 71 + -23 -8k = 71 + -23 Combine like terms: 71 + -23 = 48 -8k = 48 Divide each side by '-8'. k = -6 Simplifying k = -6
| 7+5x=-4x | | 2.1x=6.72 | | x/19.7=0609137055838 | | 27.65/100= | | 12n^7+3n^5-30n^3=0 | | 1/1-i | | =2(-3y-1)+(2y+7) | | 3.1=1.7+0.3x | | 2+4m=3m-5 | | x/7-5=- | | 9x-17=-10 | | y(5y+9)=0 | | 2/3(-2a)=6 | | 6=0.2u+0.2 | | 7x+1=5x | | 7x+4-2x=-4+31 | | 7-2y+5= | | 7X-12-18X=21 | | 3n+3=90 | | 2x+4+3x-9=40 | | X+x+50+3x=100 | | 1/3h-4(2/3h-3)=2/3h-7 | | 6a+7=4+7 | | X+x+50+3x=1000 | | 8x-2=4+2x | | 5/4-y-1/4 | | X-2=2(2x-17) | | -6a+3(11-8a)-2=0 | | 7(4-x)=112 | | 8/13=y/12 | | -7x+57=12-7(x+8) | | X^2=5n |